Health Problem of Dalit Elderly People of Shivasatakshi Municipality, Nepal - Pradip Parajuli; Sarita Bista; Dipak Ghising (Journal of Population and Development, 2026)
Health is essential to all, particularly in the context of Nepal's aging population. This paper focused on health behavior practices among elderly Dalit people. The study population consisted of elderly Dalit individuals from Shivasatakshi Municipality, Jhapa District, Koshi Province, Nepal, and a census was employed to collect quantitative data. The structural questionnaire was administered as a data collection tool. The total sample sizes are 240. The data was analyzed in the SPSS application. The physical health problems of Dalit older people have a strong association with social security allowance, according to statistical analysis (p = 0.080). An omnibus test of model coefficients, using a chi-square, yields a value of 11.279, which explains 8.8 percent of the dependent variable's variation due to cofactor variable. This finding is statistically significant (p < .001). An omnibus test of model coefficients' chi-square is 28.151, which explains 21.2 percent of the dependent variable by the cofactor variable, including the interest variable (SSA). Physical health issues and receiving Social Security Allowance (SSA) are significantly correlated, according to binary logistic regression analysis, which explains 8.8 percent of the variation in health outcomes (df=11.279, p=0.080). The results highlight the critical need for focused, gender-sensitive, and financially beneficial healthcare treatments for elderly persons who are marginalized.